(untitled) (Eurasian Research Bulletin, 2021)
Bengali is the sole official and national language of Bangladesh and one of the 22 scheduled official language, in India. English is often used secondarily in the higher tier of the judiciary in both Bangladesh and India (along with Hindi in India). Laws were written in English during the colonial periods. There are 10 English language newspapers in Bangladesh. English medium schools are also operated in English. Mainly, the people of Bengali (Bangladeshi) descent residing in the UK, Canada, Australia, New Zealand and the US and students of English medium schools in Bangladesh use “Benglish” (though Standard English is also tried to be taught). This applies to those originating from East India also.